Influence of training and education on quality improvement: evidence from electrical and electronics firms in Malaysia. - Abdullah, Muhammad Madi; Uli, Jegak (2007)
Training and education (T&Ed) is an important aspect that sustains the organizations towards continuous quality improvement. People are an organization's most valuable resource; they want to do a good job, but they do not know how, therefore management must take responsibility for helping them and organizations that are committed to quality improvement will invest heavily in training and education of their employees. T&Ed therefore becomes an important aspect in the human resource practices in the organization. The aim of the paper is to examine the unique comtribution or the influence of training & education on quality improvement in 255 Electrical and Electronics (E&E) firms in Malaysia. The finding reveals that quality improvement in these organizations was significantly influenced by training & education. Thus, this study has empirically shown that qnality improvement will increase when the firms implement more training and educational activities.